Asuhan keperawatan Jiwa pada Sdr. A dengan Masalah Utama Isolasi Sosial : Menarik Diri Akibat Skizofrenia Paranoid di Ruang Gatotkaca RSJD Dr. Amino Gondohutomo Provinsi Jawa Tegah - Nova Chairin Nisa; Slamet Wijaya; Siti Fatimah (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Schizophrenia is a severe mental disorder characterized by a decline in cognitive abilities and social skills, an inability to care for oneself, and potential brain function impairment. One of the consequences often observed in schizophrenia patients is social isolation, where the individual is unable to interact with others around them. This study aims to assess and provide psychiatric nursing care for Sdr. A, who is experiencing the primary issue of social isolation: withdrawal due to paranoid schizophrenia at the Gatotkaca ward of RSJD dr. Gondohutomo in Central Java Province. Initial assessment of the patient revealed that Sdr. A is experiencing social isolation, particularly withdrawal from their social environment. Four nursing problems were identified, including social isolation: withdrawal, low self-esteem, sensory perception disturbances such as hallucinations, and self-care deficits. A nursing care plan was developed based on the Indonesian Nursing Diagnosis Standard , Indonesian Nursing Service Standard, and Indonesian Nursing Information System , tailored to the patient's condition at the time. The care plan includes interventions to enhance social interaction, improve self-esteem, address sensory perception disturbances, and promote self-care abilities. The nursing implementation was carried out using a holistic approach involving psychosocial support and appropriate medical therapy based on the patient’s needs. It is expected that through this approach, the patient can reduce social isolation symptoms and improve their quality of life. This study emphasizes the important role of psychiatric nursing care in addressing social issues in patients with paranoid schizophrenia and how a structured nursing care plan can support patient recovery.